Pemanfaatan susu kacang pada pembuatan roti tawar dilihat dari karakteristik fisikokimianya - Benedicta Miquella Adisty Wulandari; Monika Rahardjo; Monang Sihombing (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Commercially sold white bread is often enriched with cow's milk in its formulation, which is often avoided by vegetarians. Hence the need for alternative bread products that use plant-based ingredients. Alternatives to cow's milk, namely plant-based milks, have gained popularity due to their various health benefits. Milk made from nuts has been identified as a suitable alternative for individuals allergic to cow's milk or those seeking plant-based options due to lifestyle. Therefore, this study aimed to utilize nut milk in the manufacture of white bread in terms of its physicochemical characteristics. The research method consists of four steps, namely making nut milk, making white bread, physicochemical analysis, and statistical analysis. In this study, bread texture was tested with the parameters of hardness, cohesiveness, springiness, gumminess, chewiness, fracture force, adhesive force, adhesiveness and stiffness. However, after statistical analysis using ANOVA (Analysis of Variance) on these parameters, there was parameter that did not have significant differences, namely the fracture force parameter. While in the proximate analysis, all parameters (carbohydrate, protein, fat, water, and ash) had significant differences after statistical analysis using ANOVA. It can be concluded that milk made from legumes can be utilized as an alternative to cow's milk in making bread.